Working together for impact - CGIAR Challenge Program on Water and Food (2011)
Despite challenges in many river basins, overall the planet has enough water to meet the full range of peoples’ and ecosystems’ needs for the foreseeable future, but equity will only be achieved through judicious and creative management.